Designing for the future in the age of pandemics: a future-ready design research (FRDR) process. Issue 2 (4th March 2021) - Pee, L.G.; Pan, Shan L.; Wang, Jingyuan; Wu, Junjie
ABSTRACT: The recent pandemic has painfully reminded us of the need for IS design to be informed by possible futures and conscious of undesirable futures – Within months, many of the nice-to-have IS functionalities have become must-haves; Technology solutions in response to the pandemic have raised privacy and equality concerns. Although design science research fundamentally focuses on shaping artefacts and events to create a more desirable future, there has been limited guidance on how futures should be accounted for. This article addresses the gap by integrating insights from future-oriented IS research and futures research to develop guidelines for engaging with futures throughout the design science research process. The future-ready design research (FRDR) process prompts researchers to be more aware of futures, to foster the innovative foresight for actively pursuing the preferred future, and to espouse the responsible foresight for consciously avoiding undesirable futures. The guidelines are illustrated with a design science research project on outbreak analytics and the instantiated system's subsequent adaptation and utilisation in COVID-19.